Bibliometric Analysis for Mapping Future Research About Green Accounting Publications - Wildan Dwi Dermawan; Dedi Kusmayadi; Irman Firmansyah (Jurnal Akuntansi dan Perpajakan, 2023)
The application of green accounting in companies is very important for environmental sustainability and concern for the community. This triggers researchers to discuss the impact of green accounting on companies and examine green accounting issues. This research aims to map publications on green accounting in Accounting and Auditing. To answer all research questions, the author uses a bibliometric analysis research method. Research data is taken from the dimension.ai database starting from 1984-2022. Using the data retrieval keyword green accounting, 441 documents were obtained consisting of articles, chapters, proceedings, preprints, edited books and monographs. The software used is VOSViewer. The results found that Business Strategy and the Environment is the best journal in terms of productivity, the most productive authors are Sonja Gallhofer and Jim Haslam. Topics that are frequently discussed are environmental accounting information disclosure, information disclosure, mining company, firm value. The findings of this research provide valuable knowledge for researchers, academics and practitioners regarding scientific developments related to accounting science, especially in the field of green accounting.